Performance of pressure-compensating emitters using treated sewage effluent for irrigation - Fischer Filho, Joao A. [UNESP]; Oliveira, Vinicius M. R. de; Dalri, Alexandre B. [UNESP]; Zanini, Jose R. [UNESP] (Univ Federal Campina Grande, 2016)
This study aimed to evaluate the flow variation of pressure-compensating emitters using treated sewage effluent (TSE). A drip irrigation system with four types of pressure-compensating emitters (G1 - Naan Dan Jain Model Top Drip, G2 - Naan Dan Jain Model Naan PC, G3 - Drip-Plan, G4 - Naan Dan Jain Model Naan Amnon) was installed with TSE from the sewage treatment station, filtered through a disc filter (120 mesh). Seven evaluations of flow rate of the drippers were performed (0, 100, 200, 300, 400, 500 and 600 h of operation) operating at 100 kPa. The experimental design was completely randomized in a 4 x 7 factorial arrangement (4 models and 7 times) with four replicates and Tukey test to compare the means. The relative flow rate (Qr), flow rate coefficient of variation (CVQ) and degree of clogging (DC) were determined. It was found that the models of emitters were not much susceptible to clogging during the operation of the system. The G4 model showed better performance compared with the others, presenting mean Qr of 99.92%, CVQ of 2.69% and DC of 1.19% at the end of the experiment. The results revealed that emitters are affected by the time of use of TSE.
Keywords: wastewater; trickle irrigation; clogging; water saving